Public Financial Accountability in Pakistan : The Impact of PIFRA on Capacity - Ceesay, Ismaila B. (World Bank, Washington, DC, 2012)
This paper highlights the capacity enhancement support provided under the World Bank-financed Pakistan Improvement of Financial Reporting and Auditing (PIFRA) project and six lessons learned to be considered in designing similar projects: (a) address capacity constraints at every level, that is, individual, organizational, and institutional, (b) avoid addressing an entire large country in one project, (c) avoid introducing state-of-the art technology in an environment of largely unskilled professionals, (d) avoid too many project components, (e) ensure ownership and commitment by the project agency, and (f) ensure collaboration among donors.